Penguatan Etika Digital Melalui Materi “Adab Menggunakan Media Sosial” Pada Mata Pelajaran Pendidikan Agama Islam Dalam Membentuk Karakter Peserta Didik Menghadapi Era Society 5.0 - Novita, Novita Nur Inayha (Journal of Education and Learning Sciences, 2023)
Demoralization happens in millenial generation because of the negative influence of social media. Use social media without parental control make high crimes such as gambling, creating pornographic content, bullying, fraud, sharing fake news, and radicalism. It happen as negative impact of social media. Digital ethics is needed as a guide for a person or group of people to regulate their behavior in the digital era. Awareness, Responsibility, Integrity (honesty), Virtue must be the characteristics of the millennial generation going to the era of society 5.0. This research is using a qualitative approach by descriptive method of literature analysis. Islamic Religious Education as the basis formation of characters and morals of students must be able to take preventive action to press the negative impacts from technological transformation, one of which is through the teaching of "Adab Using Social Media". Education must be able to create quality and morality human resources in society 5.0 era with the concept of a human-centered and technology-based society. Digital ethics should be integrated with all subjects in the school, remembering the urgency of digital ethics in creating a safe and comfortable digital space and respecting humanity